Butterfly Pea and Roselle Combination Extracts Reduce V-CAM, ICAM, and IL-6 Levels in High Fat Atherogenic Diet Rats - Harefa, Karnirius; Ritonga, Ahmad Hafizullah; Safitri, Riri; Aritonang, Barita; Gurusinga, Rahmad; Irmayani, Irmayani; Wulan, Sri (The Indonesian Biomedical Journal, 2024)
BACKGROUND: Atherosclerosis, driven by inflammation and oxidative stress, increases the risk of coronary heart disease (CHD). Flavonoids in butterfly pea and roselle are known for their potent antioxidant and anti-inflammatory properties. While their individual effects on cardiovascular health have been studied, no studies have explored the combined impact on atherosclerosis biomarkers, including vascular cell adhesion molecules (VCAM)-1, intercellular adhesion molecule (ICAM)-1, and interleukin (IL)-6. Therefore, this study was performed to evaluate the synergistic effects of butterfly pea and roselle combination extracts (BPRCE) on these biomarkers.METHODS: A study with a post-test control group design using 36 male white rats was performed. The rats were randomly assigned to 6 groups; 1 group was fed with standard feed, while 5 groups were fed with a high-fat atherogenic diet (HFAD) to create atherosclerosis rat models. The HFAD rats were given either no treatment, sodium carboxymethylcellulose (Na-CMC), 300, 400, or 500 mg/kgBW BPRCE. Serum levels of VCAM-1, ICAM-1, and IL-6 of rats were measured using enzyme-linked immunosorbent assay (ELISA) methods.RESULTS: Increasing doses of BPRCE resulted in a significant reduction in VCAM-1, ICAM-1, and IL-6 compared to the other groups. The group with the highest dose, 500 mg/kgBW BPRCE, showed the greatest reduction of VCAM-1 level (32.73±3.57 pg/mL), ICAM-1 level (5.68±1.17 ng/mL), and IL-6 levels (21.49±4.62 pg/mL).CONCLUSION: Administration of BPRCE in atherosclerosis rats model reduces VCAM-1, ICAM-1, and IL-6 in a dose-dependent manner. This study showed that using BPRCE as a traditional remedy for preventing and treating CHD at an optimal dose of 500 mg/kgBW might be a potential future application in reducing atherosclerosis biomarkers.KEYWORDS: VCAM-1, ICAM-1, IL-6, butterfly pea, rosella, atherosclerosis